Aesthetics and Politics A Nordic Perspective on How Cultural Policy Negotiates the Agency of Music and Arts (New Directions in Cultural Policy Research, 2018)
Through comparative and integrated case studies, this book demonstrates how aesthetics becomes politics in cultural policy. Contributors from Norway, Sweden and the UK analyse exactly what happens when art is considered relevant for societal development, at both a practical and theoretical level. Cultural policy is seen here as a mechanism for translating values, that through organized and practical aesthetical judgement lend different forms of agency to the arts. What happens when aesthetical value is reinterpreted as political value? What kinds of negotiations take place at a cultural policy ground level when values are translated and reinterpreted? By addressing these questions, the editors present an original collection that effectively centralises and investigates the role of aesthetics in cultural policy research.